Expansion of the aphid Myzocallis (Lineomyzocallis) walshii (Monell) on the red oak Quercus rubra, and adaptation of local parasitoids in the northeastern Iberian Peninsula (Hom., Aphididae, Calaphidinae; Hym., Braconidae, Aphidiinae) - Pons, X.; Lumbierres, B.; Starý, P. (Journal of Pest Science, 2005)
An ongoing expansion of Myzocallis (L.) walshii (Monell) in the NE Iberian Peninsula was detected. The aphid species was recorded in Catalonia, Andorra and Navarra. Adaptation of local native parasitoids (at least Trioxys pallidus Haliday and T. tenuicaudus Stary´) to the new immigrant was documented, together with background information on their host range in the native environments. The detection of parasitoids of M. walshii is the ﬁrst published evidence in Europe. The new evidence for M. walshii in the NE Iberian Peninsula also supports the warning of the expansion of the aphid as a pest of Quercus rubra over Europe.
Keywords: Aphids; Myzocallis walshii; Parasitoids; Quercus sp.; Trioxys pallidus; Trioxys tenuicaudus